Rules - Lord, Cynthia (New York Scholastic Press, 2006)
Frustrated at life with an autistic brother, twelve-year-old Catherine longs for a normal existence but her world is further complicated by a friendship with a young paraplegic.
Keywords: Autism -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; People with disabilities -- Juvenile fiction